Validação e reprodutibilidade da análise subjetiva no diagnóstico da cor dentária - Meireles, Sônia Saeger (2006)
The objective of this study was to examine the validity and reproducibility of the subjective evaluation used for tooth shade diagnosis. This study used the same ninety-two individuals selected for a randomized clinical trial comparing two carbamide peroxide bleaching agents. The shade of the six upper anterior teeth of these subjects was determined before starting the clinical trial. One operator performed the objective shade determination of all upper anterior teeth (n= 552) using a spectrophotometer (Vita Easyshade, VITA). Then, two calibrated examiners subjectively determined the teeth shade of the patients following their arrival time for the dental appointment. The visual (subjective) analysis was performed using a conventional shade guide (Vitapan Shade Guide, VITA). The reproducibility was evaluated using the kappa (k) coefficient, considering the shades grouped in two categories (light and dark) or using the pondered kappa (Kw), which considers all the 16 shades of the guide. The sensibility and specificity were determined using the spectrophotometer as the gold-standard. The faithful of the subjective evaluation for the two categories of shades was substantial (K= 0.69) and mild (Kw= 0.33) when considering all shades. The sensibility of the visual analysis was 86.9% and the specificity was 81.9%. The visual analysis of the shades was considered a valid method, despite the subjectivity, showing good reproducibility to differentiate light and dark shades